Case reportBehçet’s disease leaves the silk road - Woźniacka, Anna; Jurowski, Piotr; Omulecki, Anastazy; Kot, Marek; Dziankowska-Bartkowiak, Bożena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Behçet’s disease is rarely recognized among Caucasians, while it is endemic in countries of the Eastern and Central Asia, especially in Turkey. The aim of the manuscript is to present the clinical picture, diagnosis criteria and therapeutic approaches of this rare disease which, because of intensive migration, can occur not only in particular regions of the world.